Carbon dioxide emissions,urbanization and globalization:a dynamic panel data - Leitão, Nuno Carlos (2013)
This study investigates the existence of environmental Kuznets curve (EKC) for carbon dioxide (CO2) emissions and its relationship with economic growth, energy consumption and globalization over the period of 1990-2010. We apply a dynamic panel data (GMM-system estimator) using the data of selected 18 countries. This estimator permits to solve the problems of serial correlation, heteroskedasticity and endogeneity for some explanatory variables. The environmental consequences of economic growth are according to environmental Kuznets (EKC) hypothesis. Globalization seems to be a main engine that provides a way to enhance production intensively by utilizing abundant domestic resources efficiently. The energy consumption has positive impact on CO2 emissions. Urbanization improves environmental quality by lowering CO2 emissions, i.e an inverted-U shaped relationship between urbanization and CO2 emissions.